2015
DOI: 10.1186/s12968-015-0118-0
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial T2 mapping reveals age- and sex-related differences in volunteers

Abstract: BackgroundT2 mapping indicates to be a sensitive method for detection of tissue oedema hidden beyond the detection limits of T2-weighted Cardiovascular Magnetic Resonance (CMR). However, due to variability of baseline T2 values in volunteers, reference values need to be defined. Therefore, the aim of the study was to investigate the effects of age and sex on quantitative T2 mapping with a turbo gradient-spin-echo (GRASE) sequence at 1.5 T. For that reason, we studied sensitivity issues as well as technical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
64
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 31 publications
9
64
2
Order By: Relevance
“…In a study of 342 healthy subjects, native T1 values of women were higher up to the age of 45 years [70]. Similarly, a study in 74 healthy subjects revealed higher myocardial T2 in women and in subjects with greater age [47, 71]. Further insights are expected from on-going other population-based studies [72].…”
Section: Normal Valuesmentioning
confidence: 99%
“…In a study of 342 healthy subjects, native T1 values of women were higher up to the age of 45 years [70]. Similarly, a study in 74 healthy subjects revealed higher myocardial T2 in women and in subjects with greater age [47, 71]. Further insights are expected from on-going other population-based studies [72].…”
Section: Normal Valuesmentioning
confidence: 99%
“…T1 mapping was performed using modified Look-Locker imaging 30 31. For T2 mapping, a hybrid gradient and spin echo (GraSE) sequence was used at the London site,32 whereas in Frankfurt T2 mapping fast low angle shot (FLASH) sequence was employed 33 34. All sequence types and parameters have been validated and reported previously 12 18 20.…”
Section: Methodsmentioning
confidence: 99%
“…T2 maps were generated according to Bönner et al [15]. T2 maps were generated off-line using software based on the graphical programming language LabVIEW (National Instruments, Austin, TX).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we demonstrated increased T2 values in patients with biopsy-proven acute myocarditis (bpAMC) compared to age and gender matched controls [10, 15]. Furthermore, we proposed a diagnostic approach quantifying the extent of myocardium with pathologically elevated T2 time expressed as percentage of whole myocardium, thus taking accumulating regional inflammation into account.…”
Section: Introductionmentioning
confidence: 99%